2013
DOI: 10.1111/imig.12089
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Legal Norms in the EU's External Border Control

Abstract: Despite an increased level of legalization of JHA, academic literature has paid little attention to the role of law in this field. It is the objective of this article to assess the EU's attempt to reconcile its current practices of extraterritorial border control coordinated by Frontex in the Mediterranean with international human rights law, notably the principle of non-refoulement. By drawing on insights on both rationalist and constructivist accounts, we argue that international human rights principles such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…This is highly problematic. Scholars have shown that the EU legal and institutional framework has provided additional constraints for policy‐makers who aim to restrict domestic asylum policies (Slominksi, ; Zaun, , p. 24). By opting for new intergovernmental settings, Member States are again able to evade these constraints and legal guarantees and adopt policies which are normatively highly questionable (see Slominski and Trauner; Moreno Lax).…”
Section: Contribution Of This Special Issuementioning
confidence: 99%
“…This is highly problematic. Scholars have shown that the EU legal and institutional framework has provided additional constraints for policy‐makers who aim to restrict domestic asylum policies (Slominksi, ; Zaun, , p. 24). By opting for new intergovernmental settings, Member States are again able to evade these constraints and legal guarantees and adopt policies which are normatively highly questionable (see Slominski and Trauner; Moreno Lax).…”
Section: Contribution Of This Special Issuementioning
confidence: 99%
“…Acting within the EU's multilevel structures implies that national governments may lose considerable powers to supranational actors and are no longer in control of the decision-making process (Marks et al, 1996). The increased use of majority voting and other supranational dynamics may produce policy outputs that do not necessarily reflect the interests of all Member States (Kaunert and Léonard, 2012;Niemann, 2008;Slominski, 2013;Zaun, 2016). The EU may be seen as a 'liberal constraint' for Member States in their treatment of migrants (Bonjour et al, 2017).…”
Section: European and National Constraints For Member States' Actionmentioning
confidence: 99%
“…At the same time, we acknowledge that EU policy‐makers have to pursue their preferences in an increasingly legalized environment, which affects their strategies and collective interaction outcomes (Slominski, ). Though legalization does not deprive EU institutions of their political agency, it profoundly shapes the way their agency is exercised.…”
Section: Legalization and Eu Foreign Policy‐makingmentioning
confidence: 99%
“…4 This approach is based on a broad understanding of law, which enables us to take into account not only legally binding yet rather vague rules, but also the abundance of legally non-binding rules (soft law) and their interaction with one another, which can be of considerable political and legal relevance (Senden, 2004;Snyder, 1993). 5 At the same time, we acknowledge that EU policy-makers have to pursue their preferences in an increasingly legalized environment, which affects their strategies and collective interaction outcomes (Slominski, 2013). Though legalization does not deprive EU institutions of their political agency, it profoundly shapes the way their agency is exercised.…”
Section: Legalization and Eu Foreign Policy-makingmentioning
confidence: 99%